Multi-Species Probiotics Improve Health Performance and Alleviate Stress Responses of Rohu (Labeo rohita) in Inland Brackish Water Ponds - Habiba Jamil; Abdul Ghaffar; Fozia Afzal; Saima Naz; Ayesha Farooq; Maria Saeed Khan; Fuad M. Alzahrani; Khalaf F. Alsharif; Khalid J. Alzahrani; Qudrat Ullah (Probiotics and Antimicrobial Proteins, 2026)

Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.

Biochar: Acinetobacter driven rhizoremediation of arsenic contaminated soil - Maria Hameed; Muhammad Umer; Maimona Saeed; Nageen Bostan; Noshin Ilyas (Environmental Geochemistry and Health, 2026)

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

A Global Analysis of Cases of Mucormycosis Recorded in the European Confederation of Medical Mycology / International Society for Human and Animal Mycology (ECMM / ISHAM) Zygomyco.net Registry from 2009 to 2022 - Anna Skiada; Maria Drogari-Apiranthitou; Emmanuel Roilides; Jagdish Chander; Sofya Khostelidi; Nikolai Klimko; Petr Hamal; Vanda Chrenkova; Souha S. Kanj; Saeed El Zein; Katrien Lagrou; Cornelia Lass-Flörl; et al. (Mycopathologia, 2025)

An updated landscape on nanopharmaceutical delivery for mitigation of colon cancer - Maria Shahzad; Huma Hameed; Ayesha Amjad; Mahtab Ahmad Khan; Inaba Shujaat Qureshi; Anam Hameed; Asad Saeed; Rabia Munir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

A global review on perfluoroalkyl acids (PFAAs) in the riverine systems: Environmental behaviours and risks implications - Muhammad Younas; Kifayatullah Khan; Maria Zeb; Muhammad Yaseen; Noor Samad Shah; Hassan Alshemmari; Yasar N. Kavil; Saeed Saad Alelyani; Mohamed Hussien; Sidra Zeb; Di Du (Science of The Total Environment, 2025)

Anomalies in Vicker's microhardness of subbituminous and high volatile bituminous coals - Saeed Chehreh Chelgani; James C. Hower; Maria Mastalerz; Susan M. Rimmer (International Journal of Coal Geology, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

A review of heavy metals pollution in riverine sediment from various Asian and European countries: Distribution, sources, and environmental risk - Maria Zeb; Kifayatullah Khan; Muhammad Younas; Abida Farooqi; Xianghui Cao; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Abdullah G. Al-Sehemi (Marine Pollution Bulletin, 2024)

Metabolomics profiling reveals the detoxification and tolerance behavior of two bread wheat (Triticum aestivum L.) varieties under arsenate stress - Muhammad Saeed; Umar Masood Quraishi; Ghazala Mustafa; Abida Farooqi; Maria Greger; Riffat Naseem Malik (Food Chemistry, 2024)

Phenomic profiling to reveal tolerance mechanisms and regulation of ascorbate–glutathione cycle in wheat varieties (Triticum aestivum L.) under arsenic stress - Muhammad Saeed; Umar Masood Quraishi; Tommy Landberg; Maria Greger; Riffat Naseem Malik (Environmental Geochemistry and Health, 2024)

The tradeoff between water savings and salinization prevention in dryland irrigation - Saeed Karimzadeh; Sarah Hartman; Davide Danilo Chiarelli; Maria Cristina Rulli; Paolo D'Odorico (Advances in Water Resources, 2024)

Plant-based foods and hepatocellular carcinoma: A review on mechanistic understanding - Raakia Anam Saeed; Maria Maqsood; Raafia Anam Saeed; Hafiz Shehzad Muzammil; Muhammad Issa Khan; Laiba Asghar; Sahar Un Nisa; Roshina Rabail; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Exploring homologous recombination repair and base excision repair pathway genes for possible diagnostic markers in hematologic malignancies - Sumaira Fida Abbasi; Ishrat Mahjabeen; Neelam Parveen; Imama Qamar; Maria Fazal Ul Haq; Rabia Shafique; Nadia Saeed; Nida Sarosh Ashraf; Mahmood Akhtar Kayani (Molecular Genetics and Genomics, 2023)

Short-term impacts of wildfire and post-fire mulching on ecosystem multifunctionality in a semi-arid pine forest - Maria Dolores Carmona-Yáñez; Marcos Francos; Isabel Miralles; Rocio Soria; Saeed Shahabi Ahangarkolaee; Elahe Vafaie; Demetrio Antonio Zema; Manuel Esteban Lucas-Borja (Forest Ecology and Management, 2023)

Effects of interactions between natural organic matter and aquatic organism degradation products on the transformation and dissolution of cobalt and nickel-based nanoparticles in synthetic freshwater - Tingru Chang; Alexander Khort; Anher Saeed; Eva Blomberg; Maria Bille Nielsen; Steffen Foss Hansen; Inger Odnevall (Journal of Hazardous Materials, 2023)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Wake behind a Compound Wing in Ground Effect - Saeed Jamei; Adi Maimun; Rasul Niazmand Bilandi; Nor Azwadi; Simone Mancini; Luigi Vitiello; Maria De Carlini (Journal of Marine Science and Engineering, 2020)
Flow structure is a crucial point for the conceptual design of Wing-in-Ground effect (WIG) crafts. In this study, pressure distributions around a compound wing, velocity and the turbulent intensity distribution in the wake area after trailing of the wing, have been investigated numerically. Computational simulations were completed regarding various angles of attack in-ground-effect. Two parts made up the compound wing: The first composed by one rectangular wing in the center, the second composed by a reverse taper wing, consisting of an anhedral angle at the side. A realizable k-ε turbulent model exhibited the flow field in the physical domain about the wing surface. The numerical results of the compound wing were validated using the data provided by wind tunnel tests. The flow structures around the compound wing were compared with that of a rectangular wing for different conditions. It was found that the pressure distribution on the rectangular wing was weaker than at the lower surface for the compound wing. However, the suction effect on the upper surface of the rectangular wing was higher. Also, the velocity defect and the turbulence level in the wake area was greater behind the compound wing.

Synthesis and enzyme inhibitory kinetics of some novel 3-(substituted benzoyl)-2-thioxoimidazolidin-4-one derivatives as α-glucosidase/α-amylase inhibitors - Rabia Qamar; Aamer Saeed; Maria Saeed; Babar Hussain Shah; Zaman Ashraf; Qamar Abbas; Sung Yum Seo (Medicinal Chemistry Research, 2018)

Correction to: HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Muhammad Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

Seed health of organic peas and faba beans and its effects on the health of the harvested grains - Muhammad Farhan Saeed; Jelena Baćanović; Christian Bruns; Harald Schmidt; Maria Renate Finckh (Journal of Plant Diseases and Protection, 2017)

Single and Combined Impacts of Vitamin A and Selenium in Diet on Productive Performance, Egg Quality, and Some Blood Parameters of Laying Hens During Hot Season - Mohamed E. Abd El-Hack; Khalid Mahrose; Ali A. Askar; Mahmoud Alagawany; Muhammad Arif; Muhammad Saeed; Farzana Abbasi; Rab Nawaz Soomro; Farman Ali Siyal; Maria Tabassum Chaudhry (Biological Trace Element Research, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)

Budesonide Loaded PLGA Nanoparticles for Targeting the Inflamed Intestinal Mucosa—Pharmaceutical Characterization and Fluorescence Imaging - Hussain Ali; Benno Weigmann; Eva-Maria Collnot; Saeed Ahmad Khan; Maike Windbergs; Claus-Michael Lehr (Pharmaceutical Research, 2016)

Molecular docking- and genetic algorithm-based approaches to produce robust 3D-QSAR models - Reaz Uddin; Maria Saeed; Zaheer Ul-Haq (Medicinal Chemistry Research, 2014)